Healthy Nutrition of Schoolchildren of Aboriginal Population in the North - Т. V. Zhubreva (Plekhanov Russian University of Economics, 2020)
Healthy nutrition has a positive impact on human body functioning, however, the foundation of long and active life is laid in childhood and teenage years. The article provides information about using normative, technical and technological documents for organization of nutrition for schoolchildren in secondary education institutions located in places of residence of aboriginal population in the Far East. State policy concerning the development of these areas is expressed in a number of regulating documents of the federal level, where serious attention is paid to organization of hot meals for schoolchildren. On the territory of the Russian Federation ‘Rospotrebnadzor’ acts as a regulating and controlling body in the field of organization of nutrition in secondary education institutions and ‘SanPin’ is the principle regulating documents. The authors analyzed the requirements put forward by the regulator, which cannot take into account all specific features of physiology of schoolchildren’s nutrition, regional specificities and traditional nutrition culture, which underlines topicality of the research. Exclusion of traditional for Northern people food and its replacement with food typical of Central Russia cannot improve health of the rising generation. If we change this situation, it could enhance children’s health in the region and promote the development of local craft and small enterprises dealing with storing-up traditional food stuffs.